The ecology of the Tsessebe, Damaliscus lunatus lunatus, in Borakalalo National Park, North West Province. - Gopper, Byron Malcolm (University of Limpopo (Medunsa Campus), 2014)
Tsessebe are now considered rare antelope, which once occupied much of sub- Saharan Africa. Population numbers of tsessebe in Borakalalo National Park have shrunk from 43 to 13 in just 10 years. Causing great concern for park management and creating a need to determine distribution of these animals. Five vegetation communities were identified within the tsessebe’s home range. Step point method was used to determine the veld condition index for each of the identified communities. Height classes and density of woody species was determined per community. The five communities could be grouped into four major community types with two variants for community four. Veld condition index values ranged from 43.1% to 67.8%. Data downloaded from GPS/GSM collars was used to determine home ranges, distribution patterns and spatial movements within the park. Mean home range was 248 ± 49 hectares. Core ranges occurred around and along temporary water points and drainage lines. Cross-species microsatellites were used to assess genetic diversity among the tsessebe in Borakalalo National Park. In total, 36 alleles using 12 cross-species microsatellite makers were identified. The average number of alleles was 2.71 ± 1.2. The average expected heterozygosity was 0.446 ± 0.067 and average observed heterozygosity was 0.482 ± 0.047.
Thesis ( MSc ( Biology ) ) -- University of Limpopo (Medunsa Campus), 2012.
Keywords: Ecology; Tsessebe